Event MICE Sebagai Daya Tarik Pengunjung - Ramon Hurdawaty; Pusphanjali Pusphanjali (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2022)
Tourism events are planning and marketing activities that are used as communication media to introduce regional potentials such as tourist destinations and their culture with the aim of attracting tourists. Such as the event held in Bandung with the theme